Transfer of strength training to running mechanics, energetics, and efficiency - Jorge L. Storniolo; Gabriela Fischer; Renata Bona; Alexandre Pinho; Alex P. Moorhead; Marcus Tartaruga; Paula Finatto; Leonardo Peyré-Tartaruga (Termedia Publishing House, 2021)
To examine the effects of increased strength on mechanical work, the metabolic cost of transport (Cost), and mechanical efficiency (ME) during running. Fourteen physically active men (22.0 ± 2.0 years, 79.3 ± 11.1 kg) were randomized to a strength-training group (SG, n = 7), who participated in a maximal strength training protocol lasting 8 weeks, and a control group (CG, n = 7), which did not perform any training intervention. Metabolic and kinematic data were collected simultaneously while running at a constant speed (2.78 m·s-1). The ME was defined as the ratio between mechanical power (Pmec) and metabolic power (Pmet). The repeated measures two-way ANOVA did not show any significant interaction between groups, despite some large effect sizes (d): internal work (Wint, p = 0.265, d = -1.37), external work (Wext, p = 0.888, d = 0.21), total work (Wtot, p = 0.931, d = -0.17), Pmec (p = 0.917, d = -0.17), step length (SL, p = 0.941, d = 0.24), step frequency (SF, p = 0.814, d = -0.18), contact time (CT, p = 0.120, d = -0.79), aerial time (AT, p = 0.266, d = 1.12), Pmet (p = 0.088, d = 0.85), and ME (p = 0.329, d = 0.54). The exception was a significant decrease in Cost (p = 0.047, d = 0.84) in SG. The paired t-test and Wilcoxon test only detected intragroup differences (pre- vs. post-training) for SG, showing a higher CT (p = 0.041), and a lower Cost (p = 0.003) and Pmet (p = 0.004). The results indicate that improved neuromuscular factors related to strength training may be responsible for the higher metabolic economy of running after 8 weeks of intervention. However, this process was unable to alter running mechanics in order to indicate a significant improvement in ME.